Surface tension of esters. Temperature dependence of the influence parameter in density gradient theory with Peng-Robinson equation of state - Isidro Cachadiña; Ariel Hernández; Ángel Mulero (Case Studies in Thermal Engineering, 2022)
A new temperature-dependent correlation for the reduced influence parameter of the density gradient theory, when used with the Peng-Robinson equation of state, is proposed and compared with other correlations found in the literature. The proposed correlation is linear in its two fitting parameters and contains a universal exponent related to the one from the liquid-vapor phase transition universal scale law. The overall absolute deviation (OAAD) respect 1275 surface tension data for 39 esters is 1.37%. Only the proposal from Zuo and Stenby with OAAD = 1.29%, yields similar results with the same number of parameters.Fitting parameters for the new correlation proposed and those from Zuo and Stenby are given for the fluids considered in this work.